Effects of Mat Pilates online on the depressive symptoms and quality of life of older people during the COVID-19 pandemic: a randomized controlled clinical trial - Valéria Pires; Camila Miranda; Bruna Sacchi; Jonas Casagranda Zanella; Mariana de Souza Strehl; Amanda Sgarioni; Cláudia Gomes Bracht; Thaís Reichert; Ana Carolina Kanitz (Revista Brasileira de Atividade Física e Saúde)
The objective is to verify the effects of an online Mat Pilates intervention on the depressive symptoms and quality of life of older adults during the COVID-19 pandemic. This is a randomized controlled clinical trial involving 56 healthy and sedentary older adults (64.38 ± 3.45 years), randomized into two groups: Mat Pilates Training Group (PTG, n = 28) and Control Group (CG, n = 28). The intervention lasted 12 weeks, with two weekly 45-minute sessions using a video calling application. In the main part, the Basic Mat Pilates sequence was performed with progressions in the intensity, volume, and complexity of the exercises. The CG received a booklet with guidance on exercising without supervision and weekly health education lectures. Depressive symptoms were assessed using the PHQ-9 questionnaire. Quality of life was assessed using two questionnaires (WHOQOL-BREF and WHOQOL-OLD) and their respective domains. The analyses were carried out using the Generalized Estimating Equations model. In the per protocol analysis, there were no significant differences either in time (p = 0.352) or between groups (p = 0.739) for depressive symptoms (Pre: 3.50 ± 2.61 and 4.20 ± 5.92; Post: 3.08 ± 2.57 and 3.40 ± 3.86; PTG and CG respectively). No significant interactions (p = 0.969) were observed in overall quality of life (Pre: 75.00 ± 14.10 and 73.75 ± 13.76; Post: 76.04 ± 8.36 and 75.00 ± 17.68; PTG and CG respectively) nor in the domains analysis of the WHOQOL-BREF questionnaire. Regarding WHOQOL-OLD, there was an improvement in the Death and Dying domain (p = 0.042) for both groups (Pre: 70.31 ± 21.67 and 71.88 ± 20.04; Post: 79.69 ± 15.34 and 74.38 ± 23.65; PTG and CG respectively), with no interactions for overall quality of life (p = 0.820) or for the other domains. Conclusion: Remote Mat Pilates was able to maintain low levels of depressive symptoms and improve some aspects of the quality of life of older adults.